The Minnesota Haptic Function Test - Holst-Wolf, Jessica; Tseng, Yu-Ting; Konczak, Jürgen (Frontiers in Psychology, 2019)
Haptic loss severely compromises the fine motor control of many daily manual tasks. Today, no widely accepted assessments protocols of haptic function are in clinical use. This is primarily due to the scarcity of fast, objective measures capable of characterizing mild to severe forms of haptic dysfunction with appropriate resolution. This study introduces a novel curvature-perception assessment system called the Minnesota Haptic Function Test™ that seeks to overcome the shortcomings current clinical assessments. Aims: The purpose of this study was threefold: 1) Apply the test to a sample of healthy adults to establish test-specific adult norms for haptic sensitivity and acuity. 2) Establish the reliability of this instrument. 3) Demonstrate clinical efficacy in a limited sample of cancer survivors who may exhibit haptic dysfunction due to chemo-therapy induced peripheral neuropathy. Method: Participants manually explored two curved surfaces successively and made verbal judgements about their curvature. A Bayesian-based adaptive algorithm selected presented stimulus pairs based on a subject’s previous responses, which ensured fast convergence towards a threshold. Haptic sensitivity was assessed by obtaining detection thresholds in 26 adults (19-34 years). Haptic acuity was assessed by obtaining just-noticeable-difference thresholds in a second sample of 28 adults (19-25 years). Nine cancer survivors (18-25 years) with suspected peripheral neuropathy completed the acuity assessment. Test-retest reliability of the algorithm was calculated. Results: First, the test yielded values that are consistent with those reported in the literature. Mean detection threshold for curvature of the healthy adults was 0.782 (SD + 0.320 m-1). The corresponding mean discrimination threshold was 1.030 (SD + 0.462 m-1). Second, test-retest reliability of the algorithm was assessed in a simulation, yielding an average correlation between repeated simulated thresholds of r = 0.93. Third, the test documented that 86% of the cancer survivors had acuity thresholds above the 75th percentile of the normative cohort, and 29% had thresholds above the normal range indicating that the instrument can detect and differentiate between unaffected perception, and mild or more severe forms of haptic loss. Conclusion: We here provide evidence that this new method to assess haptic perception of curvature is valid, reliable, and clinically practicable.